ANALYSIS OF WORKLOAD AND NON PHYSICAL WORK ENVIRONMENT ON JOB- RELATED STRESS ON TEACHERS IN ELEMENTARY SCHOOL ENVIRONMENTS IN PANDEMIC TIMES - Ramadhan, Aan Inka; Sariasih, Sri Fatmi; Yani, Melinia Febri; Septiani, Nadya; Dewi, Syania Tantri; Hayati, Neuneung Ratna (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this study is to determine the influence of workload and non- physical work environment on elementary school teachers' job-related stress during a pandemic. The study included a poll of 68 primary school teachers who taught during the Covid-19 outbreak. Multiple Linear Regression was used to evaluate the data. The empirical tests indicate that respondents perceive an increase in workload, which leads to tremendous job stress. Simultaneously, the concept that a tremendous non-physical work environment might help minimize job-related stress is not supported. Additionally, respondents prefer face-to-face learning in the long run due to the various hurdles they confront. This study sheds light on the growth of job stress among elementary school teachers due to excessive workloads and the pressure to perform a variety of "new" activities in a short amount of time. However, generalizing the findings of this study has several limitations. The subsequent researchers can investigate with a longitudinal design to see the long-term effects of future changes in teaching and learning patterns.